2021
DOI: 10.1186/s12933-021-01359-7
|View full text |Cite
|
Sign up to set email alerts
|

Persistent clotting protein pathology in Long COVID/Post-Acute Sequelae of COVID-19 (PASC) is accompanied by increased levels of antiplasmin

Abstract: Background Severe acute respiratory syndrome coronavirus 2 (SARS-Cov-2)-induced infection, the cause of coronavirus disease 2019 (COVID-19), is characterized by acute clinical pathologies, including various coagulopathies that may be accompanied by hypercoagulation and platelet hyperactivation. Recently, a new COVID-19 phenotype has been noted in patients after they have ostensibly recovered from acute COVID-19 symptoms. This new syndrome is commonly termed Long COVID/Post-Acute Sequelae of COV… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

12
316
0
5

Year Published

2021
2021
2024
2024

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 353 publications
(403 citation statements)
references
References 76 publications
(87 reference statements)
12
316
0
5
Order By: Relevance
“…We concluded that the spike protein may have direct pathological effects on blood rheology [251]. Significant pathological changes in microcirculation and the presence of persistent microclots have also been noted in Long COVID/PASC [250].…”
Section: Covid-19mentioning
confidence: 75%
See 1 more Smart Citation
“…We concluded that the spike protein may have direct pathological effects on blood rheology [251]. Significant pathological changes in microcirculation and the presence of persistent microclots have also been noted in Long COVID/PASC [250].…”
Section: Covid-19mentioning
confidence: 75%
“…This poor prognosis is further worsened by a substantial deposition of microclots in the lungs [244][245][246]. The plasma of COVID-19 patients also carries a massive load of preformed amyloid clots and there are numerous reports of damage to erythrocytes [247][248][249] and platelets and the dysregulation of inflammatory biomarkers [240][241][242][243]250]. Recently, we also determined whether the spike protein may interfere with blood flow by comparing naïve healthy plasma samples with and without added spike protein to plasma samples from COVID-19-positive patients (before treatment).…”
Section: Covid-19mentioning
confidence: 99%
“…A possible reason might be because the extent of systemic hypercoagulation was too significant for the medication to have a substantial enough effect. Hypercoagulability, resulting in a profoundly prothrombotic state, is a distinct feature of the early stages of COVID-19 and is accentuated by a high incidence of fibrinolysis shutdown [20][21][22][23][24][25][26][27][28][29][30]. In fact, Chaudhary and co-workers in 2021 reported that all current studies support COVID-19 as a hypercoagulable and hypofibrinolytic state in the ICU setting [31].…”
Section: Introductionmentioning
confidence: 97%
“…We have also recently shown that in COVID-19, the healthy fibrinogen changes to an amyloid form (fibrin(ogen)), and that platelets are hyperactivated, and that they may form complexes with erythrocytes [21,22]. Proteomics also revealed that there are significantly dysregulated clotting proteins in microclots, including significant increases in the molecule a-(2)-antiplasmin, which prevents fibrinolysis [23].…”
Section: Introductionmentioning
confidence: 98%
“…It is unknown if arterial and venous thromboembolism and higher blood clot risk caused by insoluble micro clots during COVID-19 and in vaccinated patients can influence digital impression acquisition on deeper surfaces of a stump or implant [ 114 ]. Caution is needed because of the links between vascular damage, periodontal disease, and SARS-CoV-2 presence in oral tissues.…”
Section: Resultsmentioning
confidence: 99%